Optimization of Criminal Justice in Identifying Corruption Patterns in Government Administration and Development in Maluku - Julianus Edwin Latupeirissa; Juanrico Alfaromona Sumarezs Titahelu (Jurnal Pembangunan Hukum Indonesia, 2025)
Maluku Province, with its archipelagic characteristics, experiences the impact of corruption in nearly all its regencies and cities, where government officials often collaborate with private entities in corrupt practices. This study aims to discuss the optimization of the criminal justice system in identifying corruption patterns in government administration and development in Maluku Province. The research employs an empirical approach. The findings reveal five distinct corruption patterns in government administration and development in Maluku Province, jointly perpetrated by regional government officials and private actors. These patterns include land price manipulation, contract price inflation, overpayments, tax fraud, and fictitious activities.The study concludes that optimizing the role of the criminal justice system in identifying corruption patterns requires strengthening the institutional capacity of the Indonesian National Police (Polri) in its duties as a recipient of reports, investigator, and examiner of corruption cases. Moving forward, a more intensive coordination among all state institutions involved in criminal justice is necessary to support the government in addressing the growing issue of corruption